Natural History of Pulmonary Subsolid Nodules: A Prospective Multicenter Study - Kakinuma, Ryutaro; Noguchi, Masayuki; Ashizawa, Kazuto; Kuriyama, Keiko; Maeshima, Akiko Miyagi; Koizumi, Naoya; Kondo, Tetsuro; Matsuguma, Haruhisa; Nitta, Norihisa; Ohmatsu, Hironobu; Okami, Jiro; Suehisa, Hiroshi; et al. (Journal of thoracic oncology, 2016)
The purpose of this study was to evaluate the natural course of the progression of pulmonary subsolid nodules (SSNs). Eight facilities participated in this study. A total of 795 patients with 1229 SSNs were assessed for the frequency of invasive adenocarcinomas. SSNs were classified into three categories: pure ground-glass nodules (PGGNs), heterogeneous GGNs (HGGNs) (solid component detected only in lung windows), and part-solid nodules. The mean prospective follow-up period was 4.3 ± 2.5 years. SSNs were classified at baseline as follows: 1046 PGGNs, 81 HGGNs, and 102 part-solid nodules. Among the 1046 PGGNs, 13 (1.2%) developed into HGGNs and 56 (5.4%) developed into part-solid nodules. Among the 81 HGGNs, 16 (19.8%) developed into part-solid nodules. Thus, the SSNs at the final follow-up were classified as follows: 977 PGGNs, 78 HGGNs, and 174 part-solid nodules. Of the 977 PGGNs, 35 were resected (nine minimally invasive adenocarcinomas [MIAs], 21 adenocarcinomas in situ [AIS], and five atypical adenomatous hyperplasias). Of the 78 HGGNs, seven were resected (five MIAs and two AIS). Of the 174 part-solid nodules, 49 were resected (12 invasive adenocarcinomas, 26 MIAs, 10 AIS, and one adenomatous hyperplasia). For the PGGNs, the mean period until their development into part-solid nodules was 3.8 ± 2.0 years, whereas the mean period for the HGGNs was 2.1 ± 2.3 years (p = 0.0004). This study revealed the frequencies and periods of development from PGGNs and HGGNs into part-solid nodules. Invasive adenocarcinomas were diagnosed only among the part-solid nodules, corresponding to 1% of all 1229 SSNs.